(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The article examines the grammatical meaning of a word as a phenomenon of vocabulary in linguistic literature. It is noted that grammatical meanings are external linguistic forms of expression that are common to a number of words. It is shown that in a word the lexical meaning (individual) and grammatical meaning (general) appear in dialectical unity.